Riddick [videorecording (DVD)] - Twohy, David; Twohy, David; Diesel, Vin; Diesel, Vin; Mollà, Jordi; Nable, Matt (Universal Studios Home Entertainment, 2014)
"A dangerous, escaped convict wanted by every bounty hunter in the known galaxy, Riddick has been left for dead on a sun-scorched planet that appears to be lifeless. ... The only way off is for him to activate an emergency beacon and alert mercenaries who rapidly descend to the planet in search of their bounty"--Container.